Satisfaction of mobility students on interdisciplinary approach in awareness program for forest conservation and recycle activities. - Isa, Siti Suriawati; Mohd, Junita Shariza; Isa, Siti Salwa; Ali, Abu; Jamaludin, Nor Lelawati (Elite Scientific Publications, 2024)
In today's world, universities are encouraging students to join international mobility programs. Normally, mobility activities and programs are designed with an interdisciplinary approach to enrich the student's experience and skills. Faculty of Forestry and Environment (FFE), Universiti Putra Malaysia (UPM), has been actively using interdisciplinary design for awareness programs on forest conservation and recycling activities with mobility students from Australian and Chinese universities from 2015 until 2024. The awareness programs and recycling activities were organised using an interdisciplinary approach to provide multiple skills, experiences, and exposure to the students and other participants who came from various backgrounds. This study measures the satisfaction among participants as a guide for future mobility program design and to measure effectiveness. Mixed methods with face-to-face interviews and survey questionnaires were used to gather the data needed in this study. Data analysis for the interview extracted the main theme from the interview manuscript. While for the survey questionnaire, statistical techniques were adopted to analyse the data. The findings show Australian students are highly satisfied with the interdisciplinary awareness programs and recycling activities. The Chinese students are highly satisfied with programs and activities that have evaluation marks for them. Both groups are keen to take part in future programs organised by FFE. In conclusion, the interdisciplinary approach is one of the best methods to enhance awareness programs on forest programs and recycling activities. However, the teaching level must be at the introduction level and not too technical. Future research can look further into this topic from different aspects.